A Forgotten British War
XI, 245 p. 16 illus.
Keywords: This book presents oral histories from the last surviving UK veterans of the Korean War. With the help of the UK National Army Museum and the British Korean Society, this book collects nearly twenty testimonials of UK veterans of the Korean War. Many only teenagers when mobilized, these veterans attempt to put words to the violence and trauma they experienced. They recall the landscape and people of Korea, the political backdrop, and touching moments in unlikely situations. Like other oral histories of war, their stories recount friendship, hardship, the loss of innocence, and the perseverance of humanity in the face of cruelty. The testimonies were taken by academics and students from the University of Roehampton, and supported by the National Army Museum and the British Korean Society. Through their memories we learn a great deal about the conflict in macro and micro scales. Michael Patrick Cullinane is Professor of U.S. History at theUniversity of Roehampton, London, UK. Iain Johnston-White is Senior Lecturer in British History at the University of Roehampton, London, UK.